2017
DOI: 10.1016/j.neurobiolaging.2017.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Clinically silent Alzheimer's and vascular pathologies influence brain networks supporting executive function in healthy older adults

Abstract: Aging is associated with declines in executive function. We examined how executive functional brain systems are influenced by clinically silent Alzheimer’s disease (AD) pathology and cerebral white matter hyperintensities (WMHs). Twenty-nine younger adults and thirty-four cognitively normal older adults completed a working memory paradigm while functional magnetic resonance imaging (fMRI) was performed. Older adults further underwent lumbar cerebrospinal fluid (CSF) draw for assessment of AD pathology and FLAI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 68 publications
(78 reference statements)
1
8
0
Order By: Relevance
“…The WMH group had higher BOLD response compared to HYA during the executive contrast, which is consistent with other studies on executive function ( Gold et al, 2017 ) and spatial search tasks ( Lockhart et al, 2015 ; Gold et al, 2017 ), and is linked with white matter tract deterioration ( Madden et al, 2007 ; Persson et al, 2011 ). Unlike reports of frontal-network over-activation ( Lockhart et al, 2015 ; Gold et al, 2017 ), WMH atypically recruited highly vascularized areas of the precuneous and posterior cingulate. The precuneous, posterior cingulate cortex, and surrounding regions are a core feature of the default mode network ( McKiernan et al, 2003 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The WMH group had higher BOLD response compared to HYA during the executive contrast, which is consistent with other studies on executive function ( Gold et al, 2017 ) and spatial search tasks ( Lockhart et al, 2015 ; Gold et al, 2017 ), and is linked with white matter tract deterioration ( Madden et al, 2007 ; Persson et al, 2011 ). Unlike reports of frontal-network over-activation ( Lockhart et al, 2015 ; Gold et al, 2017 ), WMH atypically recruited highly vascularized areas of the precuneous and posterior cingulate. The precuneous, posterior cingulate cortex, and surrounding regions are a core feature of the default mode network ( McKiernan et al, 2003 ).…”
Section: Discussionsupporting
confidence: 91%
“…BOLD is a functional MRI (fMRI) approach which can probe CSVD by characterizing neurovascular signal patterns that may relate to impaired dorsal attention, default mode and fronto-parietal control networks ( Spreng et al, 2013 ). To date, however, task-based fMRI among adults with WMH has produced conflicting findings; both increased and decreased activation are reported in attentional neural networks ( Nordahl et al, 2006 ; Venkatraman et al, 2010 ; Hedden et al, 2012 ; Lockhart et al, 2015 ; Gold et al, 2017 ). Despite the utility of BOLD fMRI, challenges exist in the context of aging that influence signal-to-noise ratio and specificity of activation, be they physiological, neurovascular, or metabolic ( Huettel et al, 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the LA-MCI and LA-VD groups in our study showed higher FC between the CEN and SN, especially in the bilateral dlPFC, ventrolateral PFC, bilateral SMA, and IPL. This may due to the changes in functional compensation in LA patients with cognitive dysfunction (Lockhart et al, 2015; Gold et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is the lack of core AD biomarkers. Prior research suggested that WMH load might interact with the hallmarks of AD pathology, such as abnormal deposition of β‐amyloid (Aβ) (Gold et al, ) and tau‐protein (McAleese et al, ) in cognitively unimpaired participants. Therefore, the study of the impact of core AD pathology on the mediation effects here described represents an important topic for future research.…”
Section: Discussionmentioning
confidence: 99%